Perbandingan Cold Compress Spleen 6 dengan Endogenus Morphin Massage terhadap Nyeri Persalinan Kala 1 Fase Aktif di BPM Kota Langsa - Purwanti, Meylinda; Afdilla, Reva; Saputra, Mahruri (Lembaga Teewan Journal Solutions, 2026)
Increasing comfort and reducing labor pain in the active phase of the first stage is the main basis of this study. Labor pain causes uterine muscle weakness, birth canal obstruction and increases maternal anxiety. When the mother experiences anxiety, the production of catecholamine hormones causes pelvic muscle tension and affects the mother's pushing force during labor so that pain increases and prolongs labor time which increases the risk of maternal and fetal death. To determine the comparison of cold compress spleen 6 (sp6) with endogenous morphine (endorphin) massage on labor pain in the active phase of the first stage at BPM Langsa City. The study used a randomized control trial design with a two-group pretest-posttest design. The study was conducted from March to September 2025. The study population was mothers in the active phase of the first stage with a sample of 126e people divided into 2 groups, each of which was given cold compress SP6 and endorphin massage. The measuring instrument used was the pain numerical rating scale (PNRS) and a pain level recording sheet. The analysis used was the Wilcoxon sign rank test and Maan U Whitney. The study showed that there was a difference in the intensity of labor pain in the active phase of the first stage before and after cold compress spleen 6 (p = 0.000) and endogenous moprhin massage (p=0.000). The test results showed no difference in the intensity of labor pain in the active phase of the first stage between the cold compress spleen 6 and endogenous moprhin massage groups with a p value of 0.083. Cold compress spleen 6 and endogenous moprhin massage can stimulate the release of endorphin hormones to increase the feeling of relaxation and inhibit the transmission of pain stimuli so that it can reduce the sensation of pain in the active phase of the first stage in laboring mothers.